Perangkingan Rekomendasi Supplier Terbaik menggunakan Metode AHP dan Promethee - Marlina Marlina; Wina Yusnaeni (JURNAL TEKNIK KOMPUTER, 2021)
In the industrial world, of course, accuracy in choosing production materials is the main thing. Production materials are chosen not only in terms of the quality of the materials themselves but in terms of choosing the right supplier also determines good production. With the right selection, caution is needed. Therefore, the selection of the selection is done by using several aspects including price, quality of goods, delivery, payment methods, services, and aspects of K3L. To process the data in order to obtain an accurate ranking, namely by using AHP (Analytical Hierarchy Process) and Promethee (Preference Ranking Organization Method for Enrichment Evaluation). With these two methods, the supplier ranking will be obtained from the lowest to the highest. By getting the ranking results, it will certainly make it easier for the leader, in this case, the manager to choose the best supplier. With the selection of the best supplier, of course, the production process will run smoothly and the goods produced will have the best quality. By producing quality products, it will certainly affect the sales results later and it will greatly benefit the company.